EIDOS IN SUFI PHENOMENOLOGY: A NEW LOOK AT CREATION - Konul Bunyadzade, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
Sufi phenomenology is a new philosophical system that embraces Sufism and Husserl’s phenomenology. Eidos is one of the basic principles of this system. It underlies philosophy both in the ontological and epistemological sense. We will consider only the ontological side of this term and compare the divine and human sides in this article. The article consists of seven sections, where we consider the new approach from different prisms. First, we research the ‘Eidos in the History of Philosophy’ from Plato until Husserl. This philosophical and historical study of this term helps to analyze the need for a new approach. Eidos is an underused definition. The next section, ‘Eidos in Sufi Phenomenology’, considers the opportunities to use both its initial mean and new perspectives. One of the principal questions in an ontological sense is creation. There are two kinds of creation in Sufi Phenomenology: Divine creation and human creativity. We will consider these concepts in the sections on ‘Divine Creation and Eidos’, ‘Human Creativity and Eidos’, and on ‘Creation, Eidos, and Will’.